Evaluation method for node importance in communication networks - CHEN Yong; HU Ai-qun; HU Xiao (Tongxin xuebao)
An evaluation method for node importance in communication networks is proposed, the concise generalized expressions are given. The relative importance of two groups of nodes in the graph can be compared with respect to the number of spanning trees. The most vital nodes are those whose removal with their incident links most drastically decreases the number of spanning trees. Experimental results show that the method is simple and can reflect node importance determined by the network topology more precisely.